Aplicação dos conceitos de Lean Startup e Open Innovation na criação de startup direcionada ao ensino de empreendedorismo, cidadania fiscal, ética e contabilidade - Lucio, Ronaldo de (2019)
Study objectives: The indicators of entrepreneurship and the conditions of to undertake in Brazil, show a high index of business mortality and low educational level in entrepreneurship and innovation, to undertake without using a framework of a traditional business plan, may represent an alternative to new entrepreneurs, in this context, this applied study seeks to demonstrate the process of creating a startup based on the lean startup model and the concepts of open innovation. Design / methodology / approach: This work is of an applied nature, is a unique case study with exploratory objectives, of the unit case called GatoXadrez.com that will act in the area of education with themes of entrepreneurship, ethics, fiscal citizenship and accounting. With qualitative approach, for to analyze non quantifiable aspects and quantitative aiming for greater precision of the results. Data collection was done through: data collection by secondary and direct sources, direct observation and application of 270 questionnaires. Data analysis was performed through: content analysis, multivariate, descriptive and documentary analysis. Results: The results showed that the use of the lean startup model allowed the creation of the new company and its first MVP, favoring the process of validation of the premises and confirming its viability. The union of the lean startup model with the concepts of open innovation were also viable, as it gathered the professionals needed to develop the first product and develop the business. Practical implications: New entrepreneurs will be able to use these concepts to create companies with the minimum of financial resources, without the use of traditional business plans, using besides accounting control and gradual implementation of management controls, the accounting for innovation, which results in opportunities for success. This combination also suggests a new way of teaching entrepreneurship concepts to children from collaboration. Originality and contributions: The lean startup model propose a new way of thinking and building products and services and the concepts of open innovation can meet the demands of the new business. The work seeks to contribute to the ecosystem of entrepreneurship, with a new way of undertaking. The unit case is also relevant when seeking to teach children in a playful way, preparing them for the future, concepts of entrepreneurship, accounting, ethics and fiscal citizenship.